A Framework for implanting EITA in SMEs: Leadership, communication, project management, and change management. (Innovation & Development in Engineering and Applied Science, 2023)
One of the main problems in implanting enterprise applications in Small and Medium Enterprises (SMEs) is the lack of methodological support to guide SMEs and IT consultants in this process. Besides, there is little information about leading the implantation project, change management, leadership, and communication in an integrated way. This article's objective is to provide methodological guides that allow the implantation teams to carry out this management appropriately. This work is based on a field study and interviews with key informants who know about implanting Enterprise IT Applications (EITA) in SMEs. This research results in a descriptive framework that allows the joint management of these four transversal areas (leadership, communication, project management, and change management) and the two focus areas (processes and people).
Keywords: SImplE Framework; project management; change management; leadership; communication; ERP; CRM; LMS